Patterns of Neighboring and Predictors of Neighboring across Race: A Latent Class Analysis. Issue 4 (7th August 2020) - Gearhart, Michael C.; Bulger, Morgan; Joseph, Mark; Liu, Biwen
ABSTRACT: Residential segregation has created a stark racial and economic divide in the United States. Prior research suggests facilitating social interactions among diverse groups of neighbors is a particularly difficult – and particularly important step in addressing the legacy of segregation in the United States. This study examines patterns of neighboring across race using latent class analysis, and identifies individual characteristics associated with frequent neighboring interactions across race. We found three distinct patterns of neighboring: reluctant neighboring across race, limited neighboring across race, and actively neighboring across race. Our findings highlight the complexity of studying neighboring – particularly neighboring across race, and demonstrate that neighboring typologies warrants future research as it relates to why an individual exhibits a particular pattern of neighboring across race.